2019
DOI: 10.1016/j.nbd.2018.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Cinnamic acid activates PPARα to stimulate Lysosomal biogenesis and lower Amyloid plaque pathology in an Alzheimer's disease mouse model

Abstract: The response of the lysosomes, the waste clearance machinery of the cell, to different environmental stimuli is coordinated by a gene network with a master regulator Transcription factor EB (TFEB) at the core. Disruption of multiple facets of the lysosomal and autophagic network has been linked to various neurodegenerative and lysosomal storage disorders, making TFEB an attractive therapeutic target to rescue or augment lysosomal function under pathological scenario. In this study, we demonstrate that cinnamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
83
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(90 citation statements)
references
References 65 publications
3
83
0
4
Order By: Relevance
“…These people were characterized by lower Aβ 1-42 concentration, in comparison to age related, non-treated healthy humans (control group) [53]. The last data published by Chandra et al [54] and Chandra and Pahan [55] demonstrated that activators of PPAR-α (cinnamic acid and gemfibrozil) decrease amyloid plaque in the hippocampus and cortex in the animal model of AD (5XFAD). Moreover, they decrease neuroinflammation and thus microglia and astrocytes activation and improve spatial learning and cognition function.…”
Section: The Role Ppar-α In App/aβ Metabolismmentioning
confidence: 97%
“…These people were characterized by lower Aβ 1-42 concentration, in comparison to age related, non-treated healthy humans (control group) [53]. The last data published by Chandra et al [54] and Chandra and Pahan [55] demonstrated that activators of PPAR-α (cinnamic acid and gemfibrozil) decrease amyloid plaque in the hippocampus and cortex in the animal model of AD (5XFAD). Moreover, they decrease neuroinflammation and thus microglia and astrocytes activation and improve spatial learning and cognition function.…”
Section: The Role Ppar-α In App/aβ Metabolismmentioning
confidence: 97%
“…5xFAD mice treatment with aspirin and cinnamic acid activates TFEB gene promotor PPARGC1α and increased TFEB expression level. Elevated TFEB promotes lysosomal biogenesis and reduces Aβ plaque burden [178,179].…”
Section: Tfeb-activating Aggrephagy Inducersmentioning
confidence: 99%
“…We have demonstrated that PPARα displays a strong affinity toward compounds with long‐aliphatic side chains such as very long‐chain fatty acids including 9‐octadecenamide and hexadecanamide (Roy, Kundu, et al, ). In addition, PPARα also exhibits strong affinity toward small molecules such as statins and cinnamic acid (Chandra, Roy, Jana, & Pahan, ; Roy, Jana, Kundu, et al, ; Roy, Kundu, et al, ). This extremely diverse selection of ligands is achieved due to the amphipathic nature of LBD of PPARα.…”
Section: Resultsmentioning
confidence: 99%